Spatial and diel patterns of volatile organic compounds, DMSP-derived compounds, and planktonic microorganisms around a tropical scleractinian coral colony - Masdeu-Navarro, Marta; Mangot, Jean-François; Xue, Lei; Cabrera-Brufau, Miguel; Gardner, Stephanie G.; Kieber, David J.; González, José M.; Simó, Rafel (Frontiers in Marine Science, 2022)
Volatile organic compounds (VOCs) are constituents of marine ecosystems including coral reefs, where they are sources of atmospheric reactivity, indicators of ecosystem state, components of defense strategies, and infochemicals. Most VOCs result from sunlight-related processes; however, their light-driven dynamics are still poorly understood. We studied the spatial variability of a suite of VOCs, including dimethylsulfide (DMS), and the other dimethylsulfoniopropionate-derived compounds (DMSPCs), namely, DMSP, acrylate, and dimethylsulfoxide (DMSO), in waters around colonies of two scleractinian corals (Acropora pulchra and Pocillopora sp.) and the brown seaweed Turbinaria ornata in Mo’orean reefs, French Polynesia. Concentration gradients indicated that the corals were sources of DMSPCs, but less or null sources of VOCs other than DMS, while the seaweed was a source of DMSPCs, carbonyl sulfide (COS), and poly-halomethanes. A focused study was conducted around an A. pulchra colony where VOC and DMSPC concentrations and free-living microorganism abundances were monitored every 6 h over 30 h. DMSPC concentrations near the polyps paralleled sunlight intensity, with large diurnal increases and nocturnal decrease. rDNA metabarcoding and metagenomics allowed the determination of microbial diversity and the relative abundance of target functional genes. Seawater near coral polyps was enriched in DMS as the only VOC, plus DMSP, acrylate, and DMSO, with a large increase during the day, coinciding with high abundances of symbiodiniacean sequences. Only 10 cm below, near the coral skeleton colonized by a turf alga, DMSPC concentrations were much lower and the microbial community was significantly different. Two meters down current from the coral, DMSPCs decreased further and the microbial community was more similar to that near the polyps than that near the turf alga. Several DMSP cycling genes were enriched in near-polyp with respect to down-current waters, namely, the eukaryotic DMS production and DMS oxidation encoding genes, attributed to the coral and the algal symbiont, and the prokaryotic DMS production gene dddD, harbored by coral-associated Gammaproteobacteria. Our results suggest that solar radiation-induced oxidative stress caused the release of DMSPCs by the coral holobiont, either directly or through symbiont expulsion. Strong chemical and biological gradients occurred in the water between the coral branches, which we attribute to layered hydrodynamics.